Nerve surgery - Mackinnon, Susan E. 1950- (Thieme, 2015)
Representing the treatment and management philosophy of Dr. Susan Mackinnon, Nerve Surgery provides extensive coverage of innovative surgical options as well as guidance on the management of complicated compression neuropathies. In addition to detailed information on tried-and-true as well as cutting-edge surgical techniques, it contains chapters on the basic principles of nerve surgery, such as Anatomy and Physiology for the Peripheral Nerve Surgeon and Evaluation of the Patient with Nerve Injury or Nerve Compression